THE ROLE OF CUSTOMER SATISFACTION IN MEDIATING SERVICE QUALITY AND CUSTOMER TRUST ON CUSTOMER LOYALTY (CASE STUDY AT MELIA LAUNDRY BALI) - Awalya Rahmallah Sarija; Putu Indah Rahmawati; Trianasari Trianasari (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
The increasingly fierce competition in the laundry service industry requires business operators to retain customers by delivering quality service and building relationships based on trust. Customer loyalty is a crucial factor for business sustainability, particularly for laundry businesses that depend on repeat purchases and recommendations from customers. However, loyalty does not form instantly, as it is affected by customer experiences while using the service, including their perception of service quality and level of trust in the service provider. This situation highlights the need for empirical testing of factors that affect customer loyalty at Melia Laundry in Denpasar City. This study uses a quantitative approach with a survey method, distributing questionnaires to customers at three Melia Laundry branches. The data were analyzed using Structural Equation Modeling based on Partial Least Square (SEM-PLS) to test both direct and indirect effects among variables. The results show that service quality has a positive and significant effect on customer satisfaction and customer loyalty. Customer trust is also shown to have a positive and significant effect on customer satisfaction and customer loyalty. In addition, customer satisfaction serves as a partial mediating variable in the relationship between service quality and customer loyalty, and between customer trust and customer loyalty. These findings confirm that enhancing customer loyalty can be achieved by improving service quality and strengthening customer trust, which in turn fosters ongoing customer satisfaction.